METAL HEATING DEVICE - Kholov Orif Tolibovich; Hamdamova Lola Olimjon daughter; Gayratova Gulzoda San'at daughter (International Journal of Human Computing Studies, 2020)
Metallurgy (Greek: metallurgeo) is the study of the extraction of metals from ores or metal-containing substances and the "transfer" of properties to metal alloys; industrial sector. Extraction of metals from metal ores has long been known. Archaeological excavations show that our ancestors knew the secrets of copper mining as early as the 7th-6th centuries BC. In the 2nd millennium BC, an alloy of copper with tin - bronze - began to be used; About the middle of this millennium, iron smelting began. In this case, iron was obtained by direct heating of ores in the black at a temperature of 1100-1350 ° (the simplest method). Some time later (from the middle of the 14th century) cast iron was obtained, and later (in the 15th century) steel. The steel is made of a refractory vessel - a crucible. In the Middle Ages, they knew the secrets of making Damascus steel, a "patterned" steel with a unique structure in the East. It was used to make sharp weapons (such as swords). Information about M. can be found in the works of Abu Rayhan Beruni. Then came the Bessemer process (marten) and the Thomas process. M. as a science began to develop mainly in the second half of the 18th century. M.V. Lomonosova's 1763 book, "The Basics of Metallurgy and Ore Work," describes the foundations of M. The Russian scientist PP Anosov (1799-1851) developed the scientific basis for the production of Damascus steel. D. I. Mendeleev also made a great contribution to the development of M. science.